2021
DOI: 10.1681/asn.2020121806
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelets in Chronic Kidney Disease

Abstract: Platelet-dependent mechanisms for excessive clotting and bleeding in CKD remain undefined. Moreover, platelets’ contribution to inflammation, and specifically to CKD, are equally elusive. To date, descriptions of changes in the functional properties of circulating platelets during CKD have provided confusing interpretations. Experimental approaches that can advance our understanding of platelet dysfunction in CKD are needed, and studies that provide mechanistic insights into the dynamic relationships between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…The role of platelets in renal damage was demonstrated in the previous studies. [29][30][31][32] Talat et al showed that platelet count significantly increased in the diabetic patients. [33] The glomerulus and tubules basement membrane thickens and this leads to recruitment of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of platelets in renal damage was demonstrated in the previous studies. [29][30][31][32] Talat et al showed that platelet count significantly increased in the diabetic patients. [33] The glomerulus and tubules basement membrane thickens and this leads to recruitment of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, platelets have been found to modify the severity of inflammation directly by forming heterotypic associations with leukocytes that directly influence the immune cell phenotype such as monocyte differentiation state and cytokine release (11,12). Platelets reside at the interface of both hemostasis/thrombosis and inflammation, which makes it an ideal target for an investigation to understand better the mechanisms underlying CKD onset and progression because CKD manifests both inflammatory (heightened levels of IL-1a, IL-1b, TNF-a, non-classic monocytes in the circulation) and thrombotic (heightened levels of CD40L in the plasma) disarray (9). In many ways, CKD parallels other systemic inflammatory disorders (e.g., systemic inflammatory response syndrome and sepsis) in its presentation of wide-ranging dysregulation of hemostasis and inflammation, which negatively affects cardiorenal networks (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…With the aforementioned paradigm shift in the role of platelets, one could position these cells at a crossroads, where their pathophysiologic roles in manifesting inflammatory and thrombotic complications for patients with CKD remain unexplored (9). The most unifying concept to rectify inflammation and thrombotic complications in the CKD state is the assumption that the platelet acts as a driver of these seemingly different pathophysiologic events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations